THE ROLE OF COLLOCATIONS AND WORD FAMILIES IN STRENGTHENING B1 LEVEL VOCABULARY - Ismoilova Shakhnoza Abdumalik qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article investigates the significance of collocations and word families in developing lexical competence among B1-level EFL (English as a Foreign Language) learners. The study employs a mixed-method approach, combining pre- and post-intervention vocabulary assessments, classroom observations, and learner reflections. Findings reveal that targeted instruction in collocations and word families leads to improved vocabulary acquisition, contextual usage, and learner confidence. The article concludes with pedagogical recommendations for curriculum designers and language instructors.